Children’s Rights in the Inter-American System of Human Rights: Framework and Institutions - Zombory, Katarzyna (Children’s Rights in Regional Human Rights Systems, 2024)
The need to protect children has been a long-standing concern in the American Hemisphere, where child poverty, high rates of violence, and economic and social inequalities, particularly those affecting indigenous children, justify increased efforts to protect children and adolescents. These have led to the enshrining of children’s rights in the major human rights instruments adopted within the Inter-American system, and to the development of Inter-American private international law on children. Alongside various normative efforts, a comprehensive institutional framework, encompassing institutions specifically dedicated to protecting children’s welfare (e.g. the Inter-American Children’s Rights Institute of 1927 and the Rapporteur on the Rights of the Child of 1998), has been established. Other bodies with a general mandate to ensure the states’ compliance with human rights include the Inter-American Commission on Human Rights and the Inter-American Court of Human Rights. This paper presents a brief overview of the normative and institutional frameworks for children’s rights protection in the Inter-American human rights system.Keywords: children’s rights, child welfare, Inter-American system of human rights, Inter-American Children’s Rights Institute, Inter-American Commission on Human Rights, Inter-American Court of Human Rights